Use of infostructure for disaster: Towards definition of infostructure - Abdul Latif, Aliza; Arshad, Noor Habibah; Janom, Norjansalika (2015)
Infostructure’ is used in multiple disciplines and it carries different meaning.The variety of meaning of this term makes it hard to be applied to a specific discipline.Different definition exists and this paper is an extension work of building the definition for ‘infostructure’ to be used specifically in the area of disaster management.The earlier work had analysed existing definitions of infostructure from various disciplines, and similar definitions was searched from selected databases.In this paper, the work of building the definition is continued by analyzing the selected definitions to extract common elements and to establish the basic characteristics of infostructure tailored to disaster management.Based on these existing definitions, this paper presents the exhaustive and consistent definition for infostructure which are contrasted in 4 cases, selected from different countries that experienced different type of disaster.